KEPUASAN PELANGGAN TERHADAP LAYANAN FRONTLINE - Nova Esti Wiharsih; Efendi Efendi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2014)
This research attempts to find out whether the quality of frontliner service in CIMB Niaga Bank in Atma Jaya unit is contributing to customer satifaction. Total respondents in this research are 135 students from Atma Jaya University students. Data is analyzed with SPSS 20 with multiple regresions. Reliability, responsiveness, and tangible variabel do not influence customer satisfaction. Meanwhile, assurance and empathy have influences on customer satisfaction.